Late‐onset cerebellar abiotrophy in a Labrador Retriever. Issue 9 (4th July 2014) - Bertalan, A; Glass, EN; Kent, M; De LaHunta, A; Bradley, C
<x xml:space="preserve">Abstract</x> Case report A 5‐year‐old female spayed Labrador Retriever was examined for a hindlimb gait abnormality. Initial neurological examination was consistent with vestibular dysfunction. Over the course of 1 year, signs progressed to reflect cerebellar ataxia, vertical nystagmus and delayed postural reactions in all limbs. At the initial examination, subjective evaluation of magnetic resonance imaging scan of the brain was considered normal. Repeat imaging at 1 year after initial examination revealed a reduction in the size of the cerebellum. Retrospectively, the size of the cerebellum on the initial MRI was small when assessed using an objective measurement algorithm. Postmortem histopathological evaluation of the brain showed diffuse degeneration of Purkinje cell neurones with secondary granule cell loss in the cerebellum, in addition to pigment inclusions in brainstem neurones. Conclusion The clinical history and clinicopathological data are consistent with late‐onset cerebellar abiotrophy, which has not previously been described in this breed.